1980
DOI: 10.7164/antibiotics.33.683
|View full text |Cite
|
Sign up to set email alerts
|

New antibiotics, carbazomycins A and B. I. Fermentation, extraction, purification and physico-chemical and biological properties.

Abstract: An unidentified Streptomyces, tentatively designated as Strain H 1051-MY 10, was proved to produce viomycin and two new antibiotics. The new antibiotics were extracted from the cultured mycelia with acetone and transferred to ethyl acetate after acetone was removed in vacuo. The extracted antibiotics were separated into two components by alumina column chromatography and named carbazomycins A and B, because both antibiotics were proved to contain a carbazole nucleus. The molecular formulae of carbazomycins A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…Carbazomycin alkaloids 1 – 8 were first isolated by Nakamura and his group from Streptoverticillium ehimense H 1051-MY10 [1723] as shown in Figure 1. In addition, literature survey showed that carbazomycins A, B, C, and D have also been successfully synthesized [2427].…”
Section: Introductionmentioning
confidence: 99%
“…Carbazomycin alkaloids 1 – 8 were first isolated by Nakamura and his group from Streptoverticillium ehimense H 1051-MY10 [1723] as shown in Figure 1. In addition, literature survey showed that carbazomycins A, B, C, and D have also been successfully synthesized [2427].…”
Section: Introductionmentioning
confidence: 99%
“…Carbomycines A and B have been found to be useful as antibacterial and antifungal agents [12,13]. It has been reported that pyridocarbazoles show marked anticancer and anti-HIV activities [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Among them, carbazomycins have a simple structure, but attractive biological activities. Especially, carbazomycins A and B, which were isolated from the extract of cultured mycelia of Streptoverticillium ehimensis strain H1051-MY10 [7][8][9] (Chart 1), show inhibitory activity against 5-lipoxygenase, and have weak antibacterial and antiyeast activities. Carbazomycin B is also active against malaria.…”
mentioning
confidence: 99%